Care seeking behaviour and various delays in tuberculosis patients registered under RNTCP in Pune city - Gothankar, Jayashree Sachin; Patil, Usha Pravin; Gaikwad, Sunil R; Kamble, Sulakshana B. (Indian Journal of Community Health, 2016)
Introduction: Case finding in tuberculosis is known to be influenced by factors such as patient motivation, care seeking, the degree of diagnostic suspicion by health care provider which could result in a delayed diagnosis. Objective: To determine care seeking behaviour and delay in diagnosis and treatment of new sputum positive tuberculosis patients registered under RNTCP. Material and Methods: Descriptive cross sectional study. 283 new sputum positive tuberculosis patients (?15 years of age) registered during a period of six months at two randomly selected tuberculosis unit of Pune city. Questionnaire by WHO was modified and used. Interviews were conducted in DOT centres. Statistical analysis: Frequency, mean and standard deviation, chi square test. Results: Mean age of patients was 35 (±15) years18% of patients were unemployed and 77% resided in urban slums. The commonest co morbidity in 7.4% and 3.5 % patients was HIV/ AIDS followed by diabetics respectively. Majority of the patients, for the first and second time visited a general practitioner. Median patient, health care system and total delay were 18, 22 and 47 days with mean of 24±21, 32±30 and 56±33 days respectively. Health care system delay was less (p<0.05) in patients who first visited the public health care facility than patients who first visited a private health care provider. Conclusions: General practitioners are preferred first choice of health care provider for tuberculosis patients. Mean health care system delay is more than patient delay.